Pengaruh Profitabilitas, Solvabilitas dan Ukuran Perusahaan Terhadap Audit Report LAG - Kusnadi Kibet Lesmana (LPPM POLITEKNIK LP3I BANDUNG, 2021)
ABSTRACT This research aims to reveal, the effect of company’s profitability on audit report lag, the effect of solvability on audit report lag and the effect of company size on audit report lag of companies listed on Indonesian Stock Exchange. The data population used in this research are all the companies that are listed in BEI. The sample were takens randomly using Slovin equation, as a result, there were 115 companies choosen from the population. The data were analise using double regresion analysis. The factors that can affect audit report lag in this research are the company's internal factors including profitability, solvability and company size. Where the results of the study show, profitability has a negative effect on audit report lag, solvability has a positive effect on audit report lag, company size has a positive effect on audit report lag. Keywords: Profitabilitas, Solvabilitas, Ukuran Perusahaan and Audit Report LAG